Fluvial sedimentology of the river Ethiope sediments, Niger Delta, Southern Nigeria (Rudarsko-geološko-naftni zbornik, 2024)
Despite modern advances in the study of rivers globally, there remains a plethora of work to be done especially in the area of fluvial sedimentology of some present-day river systems. Previous studies on fluvial sedimentology of the sediments of the river Ethiope (in southern Nigeria) are meagre. Grain size analytical methods are indispensable to infer siliciclastic sediments' hydrodynamic conditions, transportation mode(s), and sedimentary environments. Twenty-eight samples (n=28) of the river Ethiope sediments were selected and studied using granulometric analyses (mechanical sieving and pebble morphometric methods). The granulometric analyses results revealed that the obtained sediments were comprised of 82.75% sand, 9.33% gravel, and 7.92% mud. A ternary diagram of sand-gravel-mud shows the sediments are mainly gravelly sand, with few indicating slightly gravelly sand, gravelly muddy sand, muddy sand, and sandy gravel. The grain size statistical analysis shows that the river Ethiope sediments consist of medium to coarse, poorly-sorted to moderately well-sorted, strongly coarse skewed to strongly fine skewed, and very platykurtic to extremely leptokurtic sands. The pebble morphometric analysis revealed that the pebbles range in shape from bladed (B) 22%, compact-bladed (CB) 17%, compact (C) 16%, compact-platy (CP) 16%, compact-elongated (CE) 12%, platy (P) 5%, to elongated (E) 5%. The integration of bivariate plots, ternary diagrams, and C-M patterns plotted for the sediments of the river Ethiope indicated a fluvial environment with sediments characterised by low to moderately high energy that transport sediments of different sizes and grades through saltation, traction, and suspension modes. This study also confirms that sediment transport modes such as saltation, traction, and suspension typify river environments. In general, the existing sedimentologic models derived from grain size analysis of sediments and pebble morphometric methods obtained from modern-day rivers can be applied to better understand transport modes, sedimentary processes, and palaeoenvironments of their ancient counterparts.